Mistletoe cottage - Mason, Debbie (Novelist) (New York : Forever, 2016)
Sophie DiRossi loved growing up in Harmony Harbor. After fleeing in disgrace many years ago, she's now left homeless by a fire and forced to move back to the small coastal town that harbors a million secrets, including her own. Looking into her daughter's eyes every day, she must keep this secret from the only man she has ever loved. Sophie's return to town is a shock for everyone, especially Liam Gallagher. In this special town at this special time of the year, Sophie and Liam can only hope for a little holiday magic.
Includes an excerpt from The trouble with Christmas.
Keywords: Homecoming -- Fiction; Secrecy -- Fiction; Christmas stories; Man-woman relationships -- Fiction; Romance fiction